Selected Training Strategies To Improve Performance In Men's Sports Swimming - Jarosław Nadobnik (Central European Journal of Sport Sciences and Medicine)
The main aim of study was to identify effective strategies to increase the endurance and stamina of professional swimmers, thereby enhancing their overall performance in long-distance or endurance swimming competitions. The study included 21 participants from swimming clubs with a mean age of 17.34 ± 2.51 years. The age range was 15 to 26 years, with varying height (172 cm to 196 cm) and weight (54 kg to 87 kg). The comprehensive study included anthropometric and isokinetic measurements, as well as training assessments analysed using statistical methods. Statistically significant changes were observed in the right arm (159.22% to 178.52%) and left arm (149.13% to 169.08% and 40.20%). There was a statistically significant improvement of 22.5 per cent in the left arm only straightening movement. The study's conclusions emphasise the importance of high-intensity exercises between 80% and 100% of maximum capacity to increase speed and power. These exercises should include significant resistance (70% to 90% of maximum load) and a limited range of repetitions (1 to 10). To develop strength and endurance, workouts should mirror the pace of a typical distance swim, incorporating moderate loads (45% to 80% of maximum body weight) and a greater range of repetitions (20 to 200).